Molecular crosstalk between ferroptosis and apoptosis: emerging role of ER stress-induced p53-independent PUMA expression - Hong, Se Hoon (Oncotarget, 2017)
Ferroptosis is a type of programmed cell death that depends on iron and is characterized by the accumulation of lipid peroxides. In the present study, we investigated the nature of the interplay between ferroptosis and other forms of cell death such as apoptosis. Human pancreatic cancer PANC-1 and BxPC-3 and human colorectal cancer HCT116 cells were treated with ferroptotic agents such as erastin and artesunate (ART) in combination with the apoptotic agent tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). We observed synergistic interaction of erastin or ART with TRAIL as determined by cell death assay, caspase activation, poly [ADP-ribose] polymerase 1 (PARP-1) cleavage, flow cytometry analysis, and lipid peroxidation assay. Moreover, erastin and ART induced endoplasmic reticulum (ER) stress and promoted p53 upregulated modulator of apoptosis (PUMA) expression via C/EBP-homologous protein (CHOP). Synergy of erastin/ART and TRAIL was abolished in PUMA-deficient HCT116 cells and CHOP-deficient mouse embryonic fibroblasts, but not in p53-deficient HCT116 cells. The results suggest the involvement of the p53-independent CHOP/PUMA axis in response to ferroptosis inducers, which may play a key role in ferroptotic agent-mediated sensitization to TRAIL-induced apoptosis.